Optimalisasi Program Pendidikan Vokasional: Meningkatkan Sikap dan Kompetensi Karier Siswa Tunarungu - Fitria, Marlenatul; Ariyati, Ika; Pardodi MABA, Aprezo (Universitas Muhammadiyah Makassar, 2024)
Deaf students have the same developmental tasks as teenagers in general, namely to be able to complete developmental tasks for teenagers aged 18-21 years who must be able to make careful considerations about their chosen career goals. The aim of this research is to determine the optimization of vocational education programs: improving the attitudes and career competencies of deaf students. The informants used in this research were 2 students in class XII SMALB B at SLB Negeri Kotagajah. This research is based on Super career maturity indicators 1) Career planning, 2) Career exploration, 3) knowledge of making career decisions, 4) career world information, 5) knowledge of preferred jobs and realism. This research uses a qualitative descriptive approach, data analysis uses Miles and Huberman. Data collection techniques using interviews, observation, documentation. The results of research on optimizing vocational education programs: improving the attitudes and career competencies of deaf students in class career world. For the dimensions of job groups preferred by deaf students, they have not yet been able to decide on a specific type of job for their career, as well as the realism dimensions which are still not suitable. Knowing this requires social support from the family, especially parents and siblings, in communicating hopes and attitudes towards future career planningKeywords: Vocational Programs, Adolescents, Attitudes and Career Competencies